2017
DOI: 10.1074/jbc.m116.769208
|View full text |Cite
|
Sign up to set email alerts
|

A Phosphoproteomic Screen Identifies a Guanine Nucleotide Exchange Factor for Rab3A Protein as a Mitogen-activated Protein (MAP) Kinase Phosphatase-5-regulated MAP Kinase Target in Interleukin 6 (IL-6) Secretion and Myogenesis

Abstract: Edited by Henrik G. DohlmanThe mitogen-activated protein kinases (MAPKs) have been shown to regulate skeletal muscle function. Previously, we showed that MAPK phosphatase-5 (MKP-5) negatively regulates myogenesis and regeneration of skeletal muscle through inhibition of p38 MAPK and c-Jun N-terminal kinase (JNK). However, the identity and contribution of MKP-5-regulated MAPK targets in the control of skeletal muscle function and regenerative myogenesis have not been established. To identify MKP-5-regulated MAP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 34 publications
(20 reference statements)
0
6
0
Order By: Relevance
“… [ 187 ] Protection from DSS-induced intestinal inflammation. [ 191 ] DUSP16 /MKP-7 Impaired GM-CSF-driven proliferation of bone marrow progenitors. [ 195 ] Increased CD4+ T-cell proliferation & a reduced Th17 cell population.…”
Section: The Inducible Nuclear Mkpsmentioning
confidence: 99%
See 1 more Smart Citation
“… [ 187 ] Protection from DSS-induced intestinal inflammation. [ 191 ] DUSP16 /MKP-7 Impaired GM-CSF-driven proliferation of bone marrow progenitors. [ 195 ] Increased CD4+ T-cell proliferation & a reduced Th17 cell population.…”
Section: The Inducible Nuclear Mkpsmentioning
confidence: 99%
“…Interestingly, the effects of DUSP10 /MKP-5 deletion on myogenesis appear to be due to two main effects. Firstly, deletion of DUSP10 /MKP-5 increases MAPK-dependent phosphorylation of guanine nucleotide exchange factor for the Ras-related protein Rab-3A Rab3A (GRAB) at Serine 169, a site required for secretion of the promyogenic cytokine IL-6 [ 191 ]. Secondly, in the absence of DUSP10 /MKP-5 increased JNK and p38 mediated phosphorylation and activation of STAT3, increases the expression of the anti-apoptotic protein B-cell lymphoma 2 (Bcl2) thus preventing apoptosis during regenerative myogenesis and also leads to improved antioxidant defence capacity due to a sustained increase in catalase expression that protects mitochondrial function [ 192 ].…”
Section: The Jnk and P38 Specific Mkpsmentioning
confidence: 99%
“…In this regard, our group recently demonstrated that MKP-5 regulates myogenesis by mediating MAPK-dependent phosphorylation of the guanine-nucleotide exchange factor for Rab3A (GRAB), which is responsible for the secretion of IL-6. MKP-5-deficient mice, as a result, express increased circulating levels of IL-6 and increased STAT3 activation [ 33 ]. Activated STAT3 couples to the apoptotic pathway by upregulating the anti-apoptotic transcription factor, Bcl-2 [ 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have implicated different kinases that regulate GRAB GEF function in various systems (Figure 1.8). For instance, the serine kinase c-Jun N-terminal kinase (JNK) has been identified to phosphorylate Ser 169 of GRAB in myocytes, promoting the secretion of the important muscle repair cytokine IL-6, however, in this study GRAB GEF function has not yet been tested (Lee and Min et al 2017). Interestingly in another publication, GRAB phosphorylation at Ser 169/180 by the neuron specific proline-directed serine/threonine membrane bound kinase Cdk5 is shown to actually decrease its GEF binding affinity to GDP-bound Rab8, modulating axon outgrowth (Furusawa and Asada et al 2016).…”
Section: Grab (Rab3il1)mentioning
confidence: 96%
“…While it is unknown if GRAB also exists in an autoinhibitory state like Rabin8, it is clear that kinases are important regulators for both of these Rab8 GEFs. (Chiba and Amagai et al 2013, Wang and Ren et al 2015, Furusawa and Asada et al 2016, Lee and Min et al 2017.…”
Section: Grab (Rab3il1)mentioning
confidence: 98%